Sequência didática para ensino e aprendizagem do conceito de força numa abordagem histórica - Nascimento, Bergson Alves do (2016)
This study had the main objective to analyze the tools that assist in the teaching and learning strength on the concept of force in physics high school. The specific objectives were: from historical accounts of the development of science in Aristotle, Descartes, Leibniz and Newton, discussing its links with the study of physics; and propose a set didactic sequence from a social interaction; and point out the different understandings of the concept of force. In order to achieve the proposed objectives, this work had as methodological procedures using the descriptive research, conducting a survey with qualitative approach. This study participated sixteen students of a 1st High School series of a private school in Aracaju, divided into four groups. The research consisted of initially applying a questionnaire to make an assessment of the students' knowledge on the subject and present the different concepts of force in view of Aristotle, Descartes, Leibniz and Newton. Subsequent to this action, met the four groups and each addressed and presented a different concept of force being applied again the questionnaire to identify the development of student learning after the completion of this interaction. The results obtained in carrying out this work show that, when using the teaching sequence with social interaction to explain physics concepts to high school students, it is observed a marked improvement in understanding of the concept of force, which often It appears as difficult to understand at first. Thus, the realization of sequence with social interaction promotes the participation of students of intensive and systematic way in the presentation of the physics content involving historical accounts also promoting a more efficient learning.